2017
DOI: 10.1016/j.stemcr.2017.03.008
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo RNAi Screen Unveils PPARγ as a Regulator of Hematopoietic Stem Cell Homeostasis

Abstract: SummaryHematopoietic stem cell (HSC) defects can cause repopulating impairment leading to hematologic diseases. To target HSC deficiency in a disease setting, we exploited the repopulating defect of Fanconi anemia (FA) HSCs to conduct an in vivo short hairpin RNA (shRNA) screen. We exposed Fancd2−/− HSCs to a lentiviral shRNA library targeting 947 genes. We found enrichment of shRNAs targeting genes involved in the PPARγ pathway that has not been linked to HSC homeostasis. PPARγ inhibition by shRNA or chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…In this regard, an increased population of adipocytes has been observed in the BM of FA patients and mouse models (Pulliam-Leath et al, 2010), probably as a consequence of FA mesenchymal stem cells preferentially differentiating as adipocytes (Zhou et al, 2017), which appear deleterious for HSC selfrenewal (Naveiras et al, 2009). Moreover, PPARG, a key regulator of adipocyte differentiation and lipid synthesis, is up-regulated in CD34 + cells from FA patients (Sertorio et al, 2017), confirming the deregulation in FA cells of lipid metabolism.…”
mentioning
confidence: 60%
“…In this regard, an increased population of adipocytes has been observed in the BM of FA patients and mouse models (Pulliam-Leath et al, 2010), probably as a consequence of FA mesenchymal stem cells preferentially differentiating as adipocytes (Zhou et al, 2017), which appear deleterious for HSC selfrenewal (Naveiras et al, 2009). Moreover, PPARG, a key regulator of adipocyte differentiation and lipid synthesis, is up-regulated in CD34 + cells from FA patients (Sertorio et al, 2017), confirming the deregulation in FA cells of lipid metabolism.…”
mentioning
confidence: 60%
“…PPARγ is an important regulator of the adipogenic program, and overexpression of PPARγ has been detected in FA patient‐derived CD34 + bone marrow cells. Dysregulated PPARγ has been suggested as a contributor to the bone marrow pathology in FA . Many studies have shown that PPARγ and the WNT/β‐catenin pathway antagonizes each other .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, an increased population of adipocytes has been observed in the BM of FA patients and mouse models (Pulliam‐Leath et al , ), probably as a consequence of FA mesenchymal stem cells preferentially differentiating as adipocytes (Zhou et al , ), which appear deleterious for HSC self‐renewal (Naveiras et al , ). Moreover, PPARG , a key regulator of adipocyte differentiation and lipid synthesis, is up‐regulated in CD34 + cells from FA patients (Sertorio et al , ), confirming the deregulation in FA cells of lipid metabolism.…”
mentioning
confidence: 81%